Effects of water and hydrogen content on the interaction mechanism between particles and the mechanical properties of a Nafion-based catalyst layer. (8th May 2019) - Li, Y; Feng, C; Qu, K N; He, P F
Abstract: A structurally stable catalyst layer and a high mobility of its internal particles are vital for the performance and lifetime of the proton exchange membrane fuel cell as a whole. However, the effects of water and hydrogen gas contents due to reaction on the physical properties of the catalyst layer are yet to be comprehensively investigated. In this study, a molecular dynamics simulation was used to study the mechanism of interaction between particles, and particle diffusion; further, the catalyst layer's mechanical properties and the change mechanism in its internal structure under deformation with different levels of water and hydrogen content were studied. The results show that when the water content increases, the interaction between the platinum particles and the graphene support is heightened, while the area of the hydrophilic regions increases, and the catalyst layer swells. The initial distances of the shells between sulfonic acid groups become longer, extending from 4.35 Å to 4.75 Å, while the diffusion capacity of the hydronium ions changes from 4.76 × 10 –9 cm 2 s −1 to 3.52 × 10 –7 cm 2 s −1 when the water content changes from λ = 1 to λ = 10. The diffusion capacity of hydronium ions reduces when the number of hydrogen molecules is less than 100 and improves when the number is more than 100. The decreased Young's modulus and yield stress, and the weaker structural stability of the catalyst layer are caused by the increase in hydrogen and water content. Owing to the hydrophilic region and the initial voids, it is easy to form large holes in the catalyst layer when it is subjected to high deformation.